Dnevi varstvoslovja, Portorož, 12. in 13. junij 2024: Zbornik povzetkov (University of Maribor Press, 2024)
25th Days of Criminal Justice and Security, Portorož, 12th & 13th of June 2024: Book of Abstracts. Contributions of the 25th Conference Days of Criminal Justice and Security offer professional and scientific reflections on the methods and resources for ensuring the security of modern society. The proceedings include summaries of six roundtables and fifty-seven abstracts, in which the authors address topics such as information security, national, private, and local aspects of ensuring internal security, the study and prevention of various forms of violence, criminal investigations, criminology, penology, and other current security challenges faced by modern society.